PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI KURSUS ANEKA SUVENIR DI PKBM INSAN MULIA DESA KEDAWONG KECAMATAN DIWEK KABUPATEN JOMBANG - Yovi Kurniawan; Ketut Atmaja (JPUS: Jurnal Pendidikan Untuk Semua, 2020)
This research is motivated by the people in Kedawong Village Diwek District Jombang Regency who feel that they still need education in the context of their existence because there are many residents who are economically including the lower middle class, seen from the lack of purchasing power and housewives who have a lot of free time. In order to provide solutions to these problems, PKBM Insan Mulia organizes community economic empowerment through various souvenir courses. This study aims to describe and analyze its implementation. The research approach chosen by the researcher is a qualitative approach to the type of descriptive research method. The results showed that the economic empowerment of the community through various souvenir courses had a positive impact on the community who participated because the learning income of citizens increased after going through the empowerment process that made the types of skills such as brooches, bags, accessories, carnival apparel, and so on. More than that, this program contributes to the preservation of out-of-school education because it is able to present solutions amid the emergence of various problems that occur in the community environment.